1998
DOI: 10.1007/s004420050414
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic responses of Microstegium vimineum (Trin.) A. Camus, a shade-tolerant, C 4 grass, to variable light environments

Abstract: Microstegium vimineum (Trin.) A. Camus, a shade-tolerant C grass, has spread throughout the eastern United States since its introduction in 1919. This species invades disturbed understory habitats along streambanks and surrounding mesic forests, and has become a major pest in areas such as Great Smoky Mountains National Park. The focus of this study was to characterize the photosynthetic induction responses of M. vimineum, specifically its ability to utilize low light and sunflecks, two factors that may be cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(109 citation statements)
references
References 39 publications
5
104
0
Order By: Relevance
“…Yet, as noted, these associations cannot fully decouple cause and effect in M. vimineum establishment. Admittedly, seed output is less likely an influence upon the abiotic environment than M. vimineum biomass; but there is an established correlation between M. vimineum vegetative biomass and seed output (Horton and Neufeld 1998, Claridge and Franklin 2002, Cheplick 2005), and we found a similar relationship (coeff. ¼ 4.8, f-value ¼ 14.47, p , 0.0006).…”
Section: Habitat Distribution and Niche Requirementssupporting
confidence: 67%
See 1 more Smart Citation
“…Yet, as noted, these associations cannot fully decouple cause and effect in M. vimineum establishment. Admittedly, seed output is less likely an influence upon the abiotic environment than M. vimineum biomass; but there is an established correlation between M. vimineum vegetative biomass and seed output (Horton and Neufeld 1998, Claridge and Franklin 2002, Cheplick 2005), and we found a similar relationship (coeff. ¼ 4.8, f-value ¼ 14.47, p , 0.0006).…”
Section: Habitat Distribution and Niche Requirementssupporting
confidence: 67%
“…Microstegium vimineum is one of many exotic species currently invading deciduous forest, understory habitats (Horton and Neufeld 1998, Cole and Weltzin 2005, Martin et al 2009 (Warren et al 2011) synthesized disparate research pertaining to potential niche limitations in M. vimineum and informed the structuring of our observational and experimental work. Most notably, the Warren et al (2011) review suggested that as multiple environmental gradients shift concurrently across woodland boundaries, individual assessment of potential niche resources (e.g., light) fails to take interactions between abiotic drivers into consideration.…”
Section: Niche and Dispersal Limitationmentioning
confidence: 99%
“…Although it is a summer annual C 4 grass, it is shade tolerant (Horton and Neufeld 1998) and tends to grow in mesic deciduous forests where it can form a dense, lawn-like monoculture underneath the canopy. In temperate regions, it recruits from seed in early spring and produces culms that can branch and root from the lowermost nodes.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Microstegium is shade tolerant and can grow in variable light conditions because of its low-light compensation points and lowdark respiration rates. These allow the plant to continue to assimilate COz in the darkness of the understory (Horton and Neufeld 1998). In fact, microstegium has been observed growing in areas that receive only 5% full sunlight Microstegium is found throughout the ORR.…”
Section: F-5mentioning
confidence: 99%